1970
DOI: 10.1002/1097-0142(197004)25:4<758::aid-cncr2820250403>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Cervical synovial sarcoma

Abstract: A case of primary cervical synovial sarcoma is presented. This is the eleventh such case to be reported. The patient is alive and free of recurrent disease or metastases 10 years following surgical resection and radiotherapy. The literature pertaining to this problem is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1973
1973
1995
1995

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…It is rarely seen in the head and neck region and some 100 cases have been reported in this region since the first case reported by Jernstrom in 1954. A review of the literature has shown only nine pharyngeal synovial sarcomas in the paediatric age group and is summarised in Table I (Cachin et al, 1966;Attie et al, 1970;Roth et al, 1975;Cutchavaree and Jimakorn, 1985;Mammelle et al, 1986;Lenoir et al, 1991). One further case of synovial sarcoma of the pharynx in the paediatric age group is reported here.…”
Section: Introductionmentioning
confidence: 67%
“…It is rarely seen in the head and neck region and some 100 cases have been reported in this region since the first case reported by Jernstrom in 1954. A review of the literature has shown only nine pharyngeal synovial sarcomas in the paediatric age group and is summarised in Table I (Cachin et al, 1966;Attie et al, 1970;Roth et al, 1975;Cutchavaree and Jimakorn, 1985;Mammelle et al, 1986;Lenoir et al, 1991). One further case of synovial sarcoma of the pharynx in the paediatric age group is reported here.…”
Section: Introductionmentioning
confidence: 67%
“…Since 1954, when Jernstrom described for the first time a synovial sarcoma in the soft tissue of the parapharyngeal region, synovial sarcomas in the cervical area were reported by the following authors: Martens, 1955;McCormack and Parker, 1956;Pricolo andCenci, 1957;Yenermen, 1958;Das andDebb, 1961; Harrison et al, 1961;Marsh et al, 1963;Cachin et al, 1966;Batsakis et al, 1967;Vande-Weghe and Kluyskens, 1968;Attie et al, 1970;Novatney and Fort, 1971; Krugman <t f a/., 1973; Fisher and Spiro, 1974;Jacobs and Weaver, 1974;Liebman et al, 1974;Minnigerode, 1974;Moussavi and Ghodsi, 1974;Gattiefa/., 1975;GoXovab et al, 1975;Mazet, 1975;Miller et al, 1975;Roth et al, 1975;Lockey, 1976;Panh et al, 1976;Chelloul and Labayle, 1977;Bertoni and Bacchini, 1978;Choux et al, 1978;Gapany-Gapanavicius et al, 1978;Junien-Lavillauroy et al, 1978;Massarelli et al, 1978;Mischler etal, 1978;Nunez-Alonso *tf a/., 1979;Setzen et al, 1979. A vaguely-defined, deep-seated and usually painless swelling is the chief presenting symptom reported in 23 cases of synovial sarcoma in the neck region (Roth et al, 1975). However, some other clinical signs (hoarseness, dysphagia, dyspnoea) may become evident, depending on the localization of the neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…A very large literature has accumulated and this was exhaustively reviewed by Moberger, Nilsonne & Friberg (1968). There have been a number of subsequent reports by Attie, Steckler & Platt (1970). Hale & Calder (1970), Gabbiani, Kaye, Lattes & Majno (1971), Roth, Enzinger & Tannenbaum (1975).…”
Section: Introductionmentioning
confidence: 99%